2020
DOI: 10.1111/ijcs.12613
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effects of mental accounting on overspending behaviour: An empirical study

Abstract: Over 40% of American households always feel like they are overspending and they regret their choices. However, these consumers are unaware of the type of overspending they follow. Such overspending behaviours include income overspending (a consumer spends more than his or her earned income), expected overspending (a consumer spends more than expected in a “normal” year) and credit overspending (a consumer does not pay off credit card balances). The study aims to explore how overspending behaviours are affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
5
0
2
Order By: Relevance
“…Notably, the money assigned in the distinct mental account is considered to be different and irreplaceable. Such a nonfungibility effect is considered the fundamental feather of mental accounting (Thaler, 1985;Sui et al, 2021). Although the operation rules of mental accounting often violate the classical economic principle of fungibility, consumers are susceptible to mental accounting when they make purchase decisions (Cheema and Soman, 2006;Xiao and O'Neill, 2018;Sui et al, 2021).…”
Section: Mental Accounting and Hedonic Consumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the money assigned in the distinct mental account is considered to be different and irreplaceable. Such a nonfungibility effect is considered the fundamental feather of mental accounting (Thaler, 1985;Sui et al, 2021). Although the operation rules of mental accounting often violate the classical economic principle of fungibility, consumers are susceptible to mental accounting when they make purchase decisions (Cheema and Soman, 2006;Xiao and O'Neill, 2018;Sui et al, 2021).…”
Section: Mental Accounting and Hedonic Consumptionsmentioning
confidence: 99%
“…Since Thaler proposed the theory of mental accounting (Thaler, 1999), a wealth of evidence has shown that consumers make purchase decisions within the limited spending and saving categories in a budget system (Arkes et al, 2008;Reinholtz et al, 2015;Hossain et al, 2018;Sui et al, 2021). Notably, consumers tend to label money based on the context in which it was obtained (Thaler, 1985;Levav and McGraw, 2009).…”
Section: Mental Accounting and Hedonic Consumptionsmentioning
confidence: 99%
“…Pengeluaran yang melebihi pendapatan dapat memicu overspending dari hasil pengeluaran yang diharapkan selama satu tahun. Situasi rumah tangga tidak dapat mengontrol pengeluaran dimana dituntut harus melunasi pembiayaan berkala maka akan memicu kredit berlebihan (Sui et al, 2021).…”
Section: Grafik 1 Penduduk Indonesia Yang Mengakses Internetunclassified
“…Overspending is strongly linked with saving, the first being influenced by wealth allocation, expenditure forecasts and saving goals (Sui et al, 2021). Some authors perceive overspending as a form of pathological spending having deep psychological roots such as depression and guilt feelings (Glatt & Cook, 1987).…”
Section: Introductionmentioning
confidence: 99%